(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The paradigm shift in higher education emphasizes the need to strengthen students’ 21st-century skills, particularly collaboration, through active learning approaches such as Project-Based Learning (PJBL). This study aims to describe students’ collaboration skills within academic projects in the Statistics for Research course. A quantitative descriptive approach was used, involving 35 students working in seven project groups. Data were collected through observation sheets and questionnaires, then analyzed using descriptive statistics. The results indicate that key collaborative aspects—shared decision-making, open communication, and active participation—were the most dominant, while support for group members and conflict resolution scored lower. These findings suggest that PJBL effectively encourages structured teamwork but still requires instructional facilitation in developing affective dimensions of collaboration. It is concluded that PJBL in statistics courses not only enhances conceptual understanding but also fosters essential collaborative soft skills needed for future professional challenges.